Effect of portlandite on ASR expansion within AAS concrete - Law, Wei Wee (2019)
The ASR expansion of alkali activated slags (AAS) mortar bars with different portlandite (Ca(OH)2) content from 0% to 25% were studied and compared with that of Ordinary Portland Cement (OPC) mortar bars. The objective was to identify the underlying effect of portlandite towards ASR behaviour within AAS concrete. Several experimental tests such as ASTM C1260 AMBT, SEM-EDX, pore solution analysis, TGA/DTA, XRD and compressive strength test have been performed. The main result shows that AAS mortar was exposed to deleterious ASR expansion when excessive portlandite content (25 wt.% of GGBFS) was added. It also showed that the magnitude of ASR expansion increased with the increase in portlandite content in AAS mortars, ensuring from the pivotal role of calcium ion from portlandite on ASR such as alkali recycling reaction and its influence on gelation process of ASR gel, as well as gel composition and gel expansion. However, when there was an absence of portlandite in AAS, innocuous ASR expansion was observed. In addition, pore solution alkalinity and binder compressive strength were not able to solely differentiate the ASR behaviours between AAS and OPC without complying the portlandite effect. Hence, it concludes that excessive amount of portlandite is crucial in bringing deleterious ASR expansion to AAS concrete especially under the compliance of high alkalinity.